2007
DOI: 10.1523/jneurosci.4622-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Signaling at A-Kinase Anchoring Proteins Organizes Anesthesia-Sensitive Memory inDrosophila

Abstract: The ubiquitous cAMP-protein kinase A (PKA) signaling pathway exhibits complex temporal requirements during the time course of associative memory processing. This directly raises questions about the molecular mechanisms that provide signaling specificity to this pathway. Here, we use Drosophila olfactory conditioning to show that divergent cAMP signaling is mediated by functionally distinct pools of PKA. One particular pool is organized via the PKA regulatory type II subunit at the level of A-kinase anchoring p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 30 publications
1
37
0
1
Order By: Relevance
“…The requirement for spaced training has been suggested to reflect the presence of a mechanistic threshold for LTM induction (Yin et al, 1994;Isabel et al, 2004) because a single training session, or even 10 training sessions, with no rest (massed training) does not form LTM . Two reports of appetitive conditioning in Drosophila using a two-trial massed procedure observed measurable levels of memory up to 24 h after training (Tempel et al, 1983;Schwaerzel et al, 2007), and we previously determined that flies trained with a 2 min odor exposure paired with sucrose revealed robust memory performance up to 6 h (Keene et al, 2006;Krashes et al, 2007). We therefore further investigated the perdurance of appetitive memory following our previously described single conditioning session protocol.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The requirement for spaced training has been suggested to reflect the presence of a mechanistic threshold for LTM induction (Yin et al, 1994;Isabel et al, 2004) because a single training session, or even 10 training sessions, with no rest (massed training) does not form LTM . Two reports of appetitive conditioning in Drosophila using a two-trial massed procedure observed measurable levels of memory up to 24 h after training (Tempel et al, 1983;Schwaerzel et al, 2007), and we previously determined that flies trained with a 2 min odor exposure paired with sucrose revealed robust memory performance up to 6 h (Keene et al, 2006;Krashes et al, 2007). We therefore further investigated the perdurance of appetitive memory following our previously described single conditioning session protocol.…”
Section: Resultsmentioning
confidence: 99%
“…disrupted after a 1 min cold-shock anesthesia administered 30 min before testing (Schwaerzel et al, 2007).…”
Section: Appetitive Ltm Is Rapidly Consolidated Within 2 H After Traimentioning
confidence: 99%
See 1 more Smart Citation
“…Kenyon cells express G-protein-coupled receptors for the monoamines that represent the US reinforcing property; both OA and DA receptors are preferentially expressed in MB neurons (Han et al, 1996(Han et al, , 1998. Whereas little is known about the intracellular biochemical events triggered by the activation of these receptors, different G-protein-coupled receptors for the monoamines might trigger distinctive molecular components, such as A-kinase anchoring proteins (Lu et al, 2007;Schwaerzel et al, 2007), that may differentiate the efficacy in inducing longer-lived memory within an overlapping set of neurons.…”
Section: Differential Us-cs Convergence Circuitries In Appetitive Andmentioning
confidence: 99%
“…Also at the molecular level, ARM and ASM can be distinguished. For instance, ASM is specifically affected in mutants with the impaired cAMP/protein kinase A (PKA) signaling pathway (e.g., rutabaga, encoding the type I adenylyl cyclase) (Dudai et al, 1988;Folkers et al, 1993;Isabel et al, 2004;Schwaerzel et al, 2007;Shuai et al, 2010). Similarly, Synapsin, a presynaptic vesicle protein essential for the regulation of the reserve pool vesicles, is preferentially required for ASM (Knapek et al, 2010).…”
Section: Introductionmentioning
confidence: 99%